Profile of students entering the nursing diploma program: University of São Paulo at Ribeirão Preto College of Nursing - Corrêa, Adriana Katia; Mello e Souza, Maria Conceição Bernardo de; Santos, Ronildo Alves dos; Clapis, Maria José; Granvile, Nilton César (Revista da Escola de Enfermagem da USP, 2011)
The objective of this study is to describe the profile of the entering students as to gender, age, marital status, educational background (elementary and high school studies) and employment status of the first class of the Nursing Teaching Diploma Program in EERP/USP, in the year 2006, highlighting their implications for the teaching-learning process. This descriptive exploratory study used a questionnaire for data collection. Results are presented in a descriptive way, with absolute and percentage frequency. The age group of the students is diverse, varying from 19 to 46 years old, most (67.5%) of them comes from public schools (high school studies), 42% work, of those, 67% already work in the health area. These data can influence in the pedagogical practice of professors.